Perancangan Sistem Informasi Tracking dan Monitoring Posisi Barang Menggunakan Metode Waterfall - Putri Tolampi, Caroline Christine; Maria, Evi (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
Information systems and information technology are essential to support a business or organization's operational and management activities. PT Vale Indonesia, one of Indonesia's largest nickel mining companies, is experiencing problems in the SCM (Supply Chain Management) Department, especially in the Shipping & Traffic Section, in tracking and monitoring the current location/position of goods. The method currently used is considered less efficient. This research aims to design an information system for tracking and monitoring the position of goods at PT Vale Indonesia. The design was carried out using the waterfall method, a system development method carried out sequentially from one phase to the next. The result of this research is the design of an information system for tracking and monitoring the position of goods, which is ready to be implemented. The test results show that all the buttons on the system function properly according to the design that has been made, making it easier to track & monitor the position of goods there.